2016
DOI: 10.1088/1742-6596/707/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and photoelectrical characteristic investigation of a new generation photodiode based on bromothymol blue dye

Abstract: Bromothymol blue (BTB) with the molecular formula of C 27 H 28 Br 2 O 5 S was grown onto p-Si substrate to fabricate heterojunction by spin coating technique. The current voltage (I-V) measurements of diode were carried out in dark and under different illumination intensity at room temperature. The photoelectrical properties of heterojunction based on BTB were investigated using the illumination intensity dependent I-V data. The results showed that photo current of diode increases with the increase in light in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…The photocurrent increases with bias voltage as a result of widening of the depletion region. The photocurrent increased with light intensity, this increasing attributed to more photon absorption and generation of electron-hole pairs in the depletion layer [21]. The linear dynamic range (LDR) of the photodetector was determined from variation of photocurrent with light intensity plot shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The photocurrent increases with bias voltage as a result of widening of the depletion region. The photocurrent increased with light intensity, this increasing attributed to more photon absorption and generation of electron-hole pairs in the depletion layer [21]. The linear dynamic range (LDR) of the photodetector was determined from variation of photocurrent with light intensity plot shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the values obtained depending on the frequency from -, for PD-5 and PD-10, the values are larger than that of obtained from -, but PD-8's are smaller. Probably, the presence of trap states and oxide layer at interfacial layer of the device and inhomogeneity that can be observed in terms of charge distributions and thickness in the interfacial layer may have caused these differences between them [45][46][47]. The same reasons may have played an important role in the differences observed in values for three samples.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 92%
“…It was shown that by using the programmed gain and synchronous detectors, the expansion of the photodiode signal bandwidth was achieved. The investigations of the optimization processes of photodiodes, described in [6], show that due to the introduction of the organic layer, a change in the photoelectric parameters of the photodiode was achieved. However, it should be noted that these works did not address the issue of increasing the accuracy of measurements, which may cause difficulties in obtaining reliable information.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%